Fresh ginger extract and salt as indirect antimicrobials for tofu - Montano, Tracy Jane G. (2003)
ABSTRACT The study determined the effect of salt and ginger extract infusion in tofu. Sensory Evaluation and Microbiological Analyses were the parameters used to assess the effects of the 2 indirect antimicrobials used in the study. It was established that the salt incorporation did not lower the microbial load of tofu. Addition of salt in freshly prepared tofu increased the TPC ascribed to the natural flora of salt. At 0.5% and 1.5% levels, salt incorporation was also shown to be favorable for the growth of the natural microbial flora of tofu like lactic acid bacteria. The TPC of test tofu samples increased through storage at refrigerated condition at about 9°C for 12 d. The Y&M of test tofu samples generally maintained a <10^-2 cfu/g during the entire 12 d storage also at refrigerated condition. Addition of ginger extract at 0.5% and 1.5% levels with salt at 0.5% to tofu did not delay the growth of microorganisms present in tofu. Both test tofu samples with ginger extract spoiled after the 5th d of storage at refrigerated condition. The tofu samples were not significantly different at 5% level of significance in terms of acceptability and descriptive ratings except for color. The gingerol, a yellowish substance present in ginger may have imparted the yellow color to the test tofu sample at 1.5% level of ginger extract. The presence of ginger extract and salt at levels used in the study did not extend the shelf-life of test tofu samples. It was recommended that higher levels of incorporation be considered to show the effects of the 2 indirect antimicrobials and initial treatments to the 2 additives to lower their natural flora.